Trade Unionism in South Africa: An interview report - Greenberg, Stanley (My University, 1974)
"Trade Unionism in South Africa" is a "working paper" of the most preliminary sort. I add that caveat not as a protection against criticism or quotation, but as genuine indication on the state of this research. This paper is based on interviewing still in progress (20 of 30 interviews are completed). The incompleteness is compounded by the mails and distance. Only six of the interview transcripts were available to me at the time of writing. The remainder were reconstructed from scattered notes and memory. Hence, my assessment of the labour movement is based on the roughest sorts of impressions and only limited access to my own data. I have imposed an artificial constraint on this paper which is not a consequence of the mails or incompleteness. I have decided to exclude nearly all historical analysis, choosing instead to concentrate on the interview material. A large percentage of my time in the last year has indeed been devoted to the examination of Trades and Labour Council records, reports and correspondence of TUCSA, various Commissions of Inquiry (particularly into industrial legislation), the role of labour in the Pact Government and subsequent governments, including the post-1948 Nationalist Government. While these materials will prove central to my later work and any future publication, they will little inform this discussion. I am afraid this report is a 'self-interested attempt on my part to make sense of some fairly diffuse, but exciting interviews.
African Studies Seminar series. Paper presented February, 1974
Keywords: Labor unions. South Africa